Augmenting a round-trip path test suite to cover all event-pairs for testing more diverse usage scenarios - Seonyeol Lee; Hyun-Jae Choi; Heung-Seok Chae (Journal of King Saud University: Computer and Information Sciences, 2023)
Among State-Based Testing (SBT) strategies, the Round-Trip Path (RTP) strategy is known to generate the most cost-effective state-based test suite. However, some studies have pointed out that an RTP suite is not sufficient because it does not test enough realistic usage scenarios, which could lead to poor fault detection. We believe that the traversal algorithm of the RTP strategy, which omits certain event-pairs, is one of the main factors causing the problem. To address this issue, we propose two methods for augmenting an RTP suite to cover all event-pairs. Through three case studies, we confirmed that the RTP suites did not cover 30%, 56.67%, and 37% of all event-pairs, some of which were critical, such as (remove, add) in an ordered set, (brake, brake) in a cruise control system, and (stop, play) in a video cassette recorder. The augmented suites improved the effectiveness of the RTP suites by testing more usage scenarios that include the event-pairs, albeit at a slightly higher cost. Compared to the All Transition-Pair (ATP) suites, the augmented suites provide a more cost-effective improvement to an RTP suite, requiring a lower cost increase rate. We believe that the augmented suites could be cost-effective alternatives between an RTP suite and an ATP suite.